PEMBATALAN PEMBERIAN HIBAH ANTARA SUAMI ISTRI YANG MELAKUKAN PERBUATAN MELAWAN HUKUM (Studi Kasus Putusan Mahkamah Agung Nomor 91/PK/Pdt/2017) - Dicky Immanuel P Kurniadi; Mia Hadiati (Fakultas Hukum Universitas Tarumanagara, 2021)
Article 1678 paragraph (1) of the Civil Code regulates the prohibition of granting between husband and wife as long as their marriage is still in progress. The problem in this research is how can the grants be canceled between husbands and wives who commit acts against the law based on the Supreme Court Decision Number 91 / PK / Pdt / 2017? The research method used is juridical normative using primary data and secondary data, and the results of research using qualitative data analysis methods. The results showed that the cancellation of grants between husband and wife who committed an illegal act was carried out through a lawsuit to the district court. Based on court facts, Denpasar District Court judges to the Supreme Court have been careful in making considerations by looking at the provisions of the laws and regulations regarding the prohibition of grants between husband and wife and exceptions as regulated in Article 1678 of the Civil Code and also the validity conditions of the grant agreement deed as regulated in Article 1320 of the Civil Code. Even though Decision Number 723 / Pdt.G / 2013 / PN.Dps rejected the Plaintiff's claim, nevertheless, the decision was in accordance with the provisions of positive law in Indonesia, resulting in legal certainty, namely the cancellation of the grant made between I Gusti Ayu Ita Dewi and Sven. Hollinger.